IMPLEMENTASI FATWA DSN-MUI PADA PRODUK ARRUM HAJI DI PEGADAIAN SYARIAH CABANG BABAKAN SURABAYA - Aulia Nabila Luthfina; A. Syifa'ul Qulub (Universitas Airlangga, 2019)
Arrum Haji products are one of the product innovations developed by Sharia Pawnshops precisely in 2016 after the banning of hajj bailout products offered by Islamic banking. In its development, Arrum Haji products cannot be separated from obstacles. One of them is that not many people know the whole product of Arrum Hajj and sharia whether or not the product. So that this study will explain the entire Arrum Haji product and review its Islamic compliance based on the provisions of the DSN-MUI Fatwa. This study uses qualitative methods with descriptive case study strategies. The object of this study is the Babakan Surabaya Islamic pawnshop. Data retrieval is done by interviewing 4 informants consisting of 3 sharia pawnshops staff Babakan Surabaya and General Secretary of the DSN-MUI in East Java. Interpretation and conclusions are made by linking between data obtained in interviews and documentation. The results showed that the Arrum Haji product was an innovation for hajj bailout products whose operations had followed the provisions of the DSN-MUI fatwa. Arrum Haji products are not the same as hajj bailout products, because both have different ujrah systems.Keywords: Shari’a Pawnshop, Arrum Haji Products, Sharia Compliant, DSN-MUI